Proceedings of the International Conference on Human-centric Computing 2011 and Embedded and Multimedia Computing 2011 HumanCom & EMC 2011 - Park, Jame J.; Jin, Hai.; Liao, Xiaofei; Zheng, Ran.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Proceedings of the International Conference on Human-centric Computing and Embedded and Multimedia Computing (HumanCom & EMC 2011) will cover topics of HumanCom and EMC, the current hot topics satisfying the world-wide ever-changing needs. Human-centric computing is to create novel solutions so that the humans are always connected, portable, and available. As with pervasive-computing, human-centric computing requires a variety of devices; however, such devices exist simply to obtain inputs from the human and are embedded in objects that humans interact with on a daily basis. Moreover, during the past couple of decades, Information Science technologies influenced and changed every aspect of our lives and our cultures. Without various Information Science technology-based applications, it would be difficult to keep information stored securely, to process information efficiently, and to communicate conveniently. Embedded computing ranges from portable devices such as digital watches and MP3 players, to large stationary installations like traffic lights, factory controllers, or the systems controlling nuclear power plants. Complexity varies from low, with a single microcontroller chip, to very high with multiple units, peripherals and networks mounted inside a large chassis or enclosure. Multimedia computing covers multimedia I/O devices, OS, storage systems, streaming media middleware, continuous media representations, media coding, media processing, etc., and also includes multimedia communications; real-time protocols, end-to-end streaming media, resource allocation, multicast protocols, and multimedia applications; databases, distributed collaboration, video conferencing, 3D virtual environments.
Keynote Speech -- HumanCom 2011 -- Session 1: Computer-assisted Learning, Cognition and Semantic Systems -- Session 2: Human-computer Interaction and Social Computing -- Session 3: Network or distributed algorithms, applications -- Session 4: Privacy, Security and trust management -- Session 5: Ubiquitous computing, mobile systems and applications -- Session 6$1!+:(BVirtualization Technologies for Desktop Applications -- EMC 2011 -- Session 1: Cyber-Physical Systems and Real-time systems -- Session 2: Distributed Multimedia Systems -- Session 3: Embedded Systems, Software and Applications -- Session 4: Multimedia Computing & Intelligent Services -- PDC 2011 -- ENC 2011.s
Keywords: Computer science; Multimedia systems; Computer vision; Telecommunication; Computer Science; User Interfaces and Human Computer Interaction; Communications Engineering, Networks; Image Processing and Computer Vision; Multimedia Information Systems